Randomized, double‐blind, placebo‐controlled dose‐finding study of the dipeptidyl peptidase‐4 inhibitor linagliptin in pediatric patients with type 2 diabetes. Issue 4 (24th November 2017) - Tamborlane, William V; Laffel, Lori MB; Weill, Jacques; Gordat, Maud; Neubacher, Dietmar; Retlich, Silke; Hettema, Willem; Hoesl, Cornelia E; Kaspers, Stefan; Marquard, Jan
Abstract : Objective: To identify the dose of the dipeptidyl peptidase‐4 (DPP‐4) inhibitor linagliptin in pediatric patients with type 2 diabetes (T2D). Methods: Double‐blind, randomized, controlled parallel group study comparing linagliptin 1 and 5 mg once daily, with placebo in 39 patients with T2D aged 10 to below 18 years. The primary efficacy endpoint was the change from baseline in glycated hemoglobin (HbA1c) after 12 weeks of treatment. The key pharmacodynamic endpoint was DPP‐4 inhibition during steady‐state. Results: Compared to placebo, there was a dose‐dependent reduction in mean HbA1c of 0.48% and 0.63% with linagliptin 1 and 5 mg, respectively, associated with corresponding declines in mean fasting plasma glucose (FPG) of 5.6 and 34.2 mg/dL. Median DPP‐4 inhibition was 38% with linagliptin 1 mg and 79% with linagliptin 5 mg. Geometric mean trough levels of linagliptin were 3.80 and 7.42 nmol/L in the 1 and 5 mg groups, respectively; levels that were slightly higher than in adult patients with T2D that were most likely caused by higher plasma DPP‐4 concentrations in the study population. There were no drug‐related adverse events during treatment with either dose of linagliptin. Conclusions: Linagliptin was well tolerated and induced dose‐dependent DPP‐4 inhibition that was accompanied by corresponding reductions in HbA1c and FPG levels in young people with T2D. The results are consistent with the clinical efficacy and safety profile that have been reported for linagliptin in adult patients with T2D, favoring linagliptin 5 mg over 1 mg.